Improving of bowel cleansing effect for polyethylene glycol with ascorbic acid using simethicone: A randomized controlled trial. Issue 28 (July 2016) - Yoo, In Kyung; Jeen, Yoon Tae; Kang, Seung Hun; Lee, Jae Hyung; Kim, Seung Han; Lee, Jae Min; Choi, Hyuk Soon; Kim, Eun Sun; Keum, Bora; Chun, Hoon Jai; Lee, Hong Sik; Kim, Chang Duck
Abstract: Background and Aim: Low-volume polyethylene glycol with ascorbic acid (PEG-Asc) use is reported to be as safe and effective as traditional 4-L polyethylene glycol use. However, PEG-Asc produces bubbles, which cause problems during colonoscopy. Data on the effects of using antifoaming agents such as simethicone with PEG-Asc are lacking. The aim of this CONSORT-prospective, randomized, observer-blinded, controlled trial is to compare the quality of bowel preparation and compliance between PEG-Asc users and PEG-Asc plus simethicone users. Methods: Adult outpatients aged 18 to 80 years undergoing colonoscopy were recruited to the study. Two hundred sixty patients were randomly assigned to 1 of 2 treatment arms, PEG-Asc or PEG-Asc plus simethicone. The primary outcome measure was the bowel cleansing quality using Boston bowel preparation scale and bubble scores. The secondary outcome measures were patient tolerability and doctor tolerability. Results: The simethicone group showed superior cleansing results (6–9 Boston scale scores: 99% vs. 84%, <5% bubble scores: 96% vs. 49%, P  < 0.001) and fewer gastrointestinal symptoms (abdominal fullness: 24% vs. 55%, colicky pain: 5% vs. 24%, P  < 0.001) than the non-simethicone group. Moreover, endoscopist fatigue during colonoscopy was lower in the simethicone group than in the non-simethicone group (1.31 ± 0.75 vs. 2.97 ± 2.14, P  < 0.001). Conclusion: PEG-Asc plus simethicone use was more effective and associated with better patient and endoscopist tolerance than PEG-Asc use. Therefore, this combination is recommended as one of the promising methods for bowel preparation before colonoscopy.